Comparison of the Immunotherapy Response Evaluation Criteria in Solid Tumours (iRECIST) with RECIST for capturing treatment response of patients with metastatic urothelial carcinoma treated with pembrolizumab. (6th August 2020) - Fukuokaya, Wataru; Kimura, Takahiro; Yanagisawa, Takafumi; Kimura, Shoji; Tsuzuki, Shunsuke; Koike, Yuhei; Iwamoto, Yuya; Enei, Yuki; Tanaka, Masatoshi; Urabe, Fumihiko; Onuma, Hajime; Honda, Mariko; et al.
Abstract : Objective: To evaluate the clinical usefulness of Immunotherapy Response Evaluation Criteria in Solid Tumours (iRECIST) in patients with metastatic urothelial carcinoma (UC) treated with pembrolizumab. The iRECIST is designed to accurately capture the tumour response treated with immunotherapy. Patients and methods: We conducted a multicentre retrospective study evaluating the clinical utility of iRECIST in 91 patients with metastatic UC treated with second‐line pembrolizumab. The objective response (OR) and time to progression (TTP) in accordance with both iRECIST and RECIST version 1.1 were compared with overall survival (OS) and risk of all‐cause mortality, and analysed using log‐rank and multivariable Cox regression models, respectively. Predictive performance of the criteria was studied using Harrell's concordance index (c‐index). The clinical usefulness of each criterion was compared using decision curve analysis. Results: Of 57 patients with progressive disease per RECIST, a considerable number of patients were reclassified to immune stable disease (six, 10.5%), immune partial response (two, 3.5%), and immune complete response (two, 3.5%) per iRECIST. Multivariable Cox regression models showed that both OR (hazard ratio [HR] 0.10, 95% confidence interval [CI] 0.03–0.35; P  = 0.001) and TTP (HR 0.59, 95% CI 0.46–0.77; P  < 0.001) per iRECIST were significantly associated with all‐cause mortality. Furthermore, iRECIST had a significant, increased predictability of OS compared with RECIST (OR, c‐index: 0.70, increase: 0.04, P  = 0.046; TTP, c‐index: 0.88, increase: 0.07, P  = 0.039). On decision curve analysis, iRECIST presented better net benefit gains than did RECIST. Conclusions: Compared with RECIST, iRECIST could more accurately predict OS of patients with metastatic UC treated with pembrolizumab. The iRECIST has the potential to be a new standard for tumour response evaluation of these patients.